PENGARUH CSR DAN GCG TERHADAP KINERJA KEUANGAN DENGAN ASIMETRI INFORMASI SEBAGAI VARIABEL MODERASI (Pada Perusahaan Perbankan yang Terdaftar Di BEI Tahun 2020-2023) - Ima Nur Aini; Djoko Kristianto (STIE AUB Surakarta, 2025)
This study aims to analyze the effect of corporate social responsibility and good corporate governance on financial performance, with information asymmetry as a moderating variable. The population in this study were banking sub-sector companies listed on the Indonesia Stock Exchange during the 2020-2023 period, totaling 44 companies. This study uses a quantitative approach with secondary data as a data source. The sampling technique used was the purposive sampling method, namely the selection of samples based on certain criteria, so that 26 samples of companies that met the criteria were obtained with a total of 104 observations during the four years of the study. The data analysis methods in this study were Descriptive Statistical Analysis, Multiple Linear Regression Analysis, Classical Assumption Test, Hypothesis Test and Moderated Regression Analysis (MRA) Test. The results showed that CSR and the board of directors had a significant effect on financial performance. However, the independent board of commissioners did not show a significant effect on financial performance. While the moderating variable, namely information asymmetry, was unable to moderate the effect of Corporate Social Responsibility, the independent board of commissioners and the board of directors on financial performance.